Psychological Challenges Experienced by EFL Students in Learning English - Eliza, Jihan; Wachyunni, Sri; Arif, Nely (Jurnal Sains Sosio Humaniora, 2023)
This study aimed to look into the psychological challenges EFL students faced while learning English and the strategies they used. This research was conducted using a quantitative descriptive research design with a questionnaire as the instrument. The respondents of this research were 75 students from one of the public junior high schools in Kota Jambi. The data obtained were analyzed using statistics and descriptive methods. Students face three psychological challenges: self-belief, motivation, and Anxiety. For the learning strategy, there were eight indicators of the learning strategy that students used in learning English; 6 of them were the learning strategy that they used, such as cognitive strategies (underlining and memorizing) and behavioral strategies (test-taking, help-seeking, homework management, and note-taking skills).